2023
DOI: 10.1002/ange.202302253
|View full text |Cite
|
Sign up to set email alerts
|

Co0−Coδ+ Interface Double‐Site‐Mediated C−C Coupling for the Photothermal Conversion of CO2 into Light Olefins

Abstract: Solar-driven CO 2 hydrogenation into multicarbon products is a highly desirable, but challenging reaction. The bottleneck of this reaction lies in the CÀ C coupling of C 1 intermediates. Herein, we construct the CÀ C coupling centre for C 1 intermediates via the in situ formation of Co 0 À Co δ + interface double sites on MgAl 2 O 4 (CoÀ CoO x /MAO). Our experimental and theoretical prediction results confirmed the effective adsorption and activation of CO 2 by the Co 0 site to produce C 1 intermediates, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Co–CoO x /MgAl 2 O 4 achieved a C 2–4 yield of 1303 μmol g −1 h −1 under light irradiation. 118 The selectivity of C 2–4 total organic carbon reached 62.5%, and the ratio of olefin to alkane reached approximately 11. Experimental and theoretical results confirmed that the two active sites at the interface effectively adsorbed and activated CO 2 to form C1 intermediates through the Co 0 site.…”
Section: Photothermal Catalytic C1 Conversion Using Supported Metal C...mentioning
confidence: 96%
“…Co–CoO x /MgAl 2 O 4 achieved a C 2–4 yield of 1303 μmol g −1 h −1 under light irradiation. 118 The selectivity of C 2–4 total organic carbon reached 62.5%, and the ratio of olefin to alkane reached approximately 11. Experimental and theoretical results confirmed that the two active sites at the interface effectively adsorbed and activated CO 2 to form C1 intermediates through the Co 0 site.…”
Section: Photothermal Catalytic C1 Conversion Using Supported Metal C...mentioning
confidence: 96%
“…13,14 The widespread applications of this technology necessitates an effective catalyst that simultaneously fulfills the requirement of high activity, exceptional durability, and cost-effectiveness to satisfy practical requirements. 15 For this purpose, a diverse range of materials have been investigated as potential catalysts for photopromoted CO 2 hydrogenation, including noble metals (e.g., Ir, Ru, Pt, and Pd) 16−19 or nonprecious metals (e.g., Cu, Co, and Ni) 14,20,21 deposited on various supports. Among these catalysts, Ru-based nanomaterials have garnered extensive recognition as the most promising catalysts for catalytic CO 2 methanation; however, the limited availability and cost-prohibitive nature of Ru pose significant constraints on their practical industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, photopromoted thermocatalytic CO 2 reduction, employing green H 2 derived from renewable energy sources, for the production of fuels or chemicals under mild conditions presents a promising pathway to effectively alleviate global warming and mitigate energy scarcity issues. , The widespread applications of this technology necessitates an effective catalyst that simultaneously fulfills the requirement of high activity, exceptional durability, and cost-effectiveness to satisfy practical requirements . For this purpose, a diverse range of materials have been investigated as potential catalysts for photopromoted CO 2 hydrogenation, including noble metals (e.g., Ir, Ru, Pt, and Pd) or nonprecious metals (e.g., Cu, Co, and Ni) ,, deposited on various supports. Among these catalysts, Ru-based nanomaterials have garnered extensive recognition as the most promising catalysts for catalytic CO 2 methanation; however, the limited availability and cost-prohibitive nature of Ru pose significant constraints on their practical industrial applications. , In this context, the incorporation of a nonprecious transition metal into Ru-forming alloys to mitigate Ru consumption represents an appealing strategy.…”
Section: Introductionmentioning
confidence: 99%